Tudley didn't know - Himmelman, John. (Mt. Pleasant, SC : Sylvan Dell Pub., 2006)
A "story about a pond-living painted turtle who adopts other animals' behaviors, simply because he doesn't know he can't! Tudley flies like a bird, sings like a katydid, hops like a frog, and glows like a firefly. He uses all his special behaviors to help other animals. Will Tudley's friends help him when he needs help? ... The 'Creative minds' section includes crafts and information about animal adaptations and their habitats"--From publisher.
Adult 520
Accelerated Reader AR
Keywords: Painted turtle -- Juvenile fiction; Animal behavior -- Juvenile fiction; Friendship -- Juvenile fiction; Painted turtle -- Fiction; Turtles -- Fiction